Genetic relationships in Saccharum complex germplasm collections based on morphological and molecular markers - Wiwit Budi WIDYASARI; . DAMANHURI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2021)
Sugarcane has a high degree of heterozygosity and is a cross-pollinator, so information about the genetic relationship between the accessions in germplasm collections is very important for selecting the prospective parent in crossbreeding. This research aims to determine the phylogenetic relationship of 24 Saccharum complex accessions and to verify the grouping of accessions using 37 morphological and three microsatellite molecular markers. Interpretation of morphological and molecular data was obtained from the analysis using the NTYSYpc-2.02i program. The results show that within the 24 accessions analyzed using morphological markers, some accessions did not cluster as the classification at the conservation time. This difference is due to the morphological markers, so the value of genetic similarity among accessions analyzed is increased. In contrast, the grouping of molecular markers shows that each accession was grouped according to the classification at the conservation time. These accessions had a low genetic similarity of 0.20 with a broad genetic distance of 0.80. This broad genetic distance indicates that the twenty-four accessions have a distant genetic relationship with one another, so that the genetic diversity of these accessions is relatively high. The high genetic diversity in germplasm collections improves its potential as a crossing parent to obtain a high heterosis effect.